Cardiac Arrest and Cardiopulmonary Resuscitation - Nolan, Jerry P. (Seminars in Neurology, 2017)
In this review, the author summarizes the incidence, causes, and survival associated with out-of-hospital cardiac arrest (OHCA) and in-hospital cardiac arrest (IHCA). The resuscitation guideline process is outlined, and the impact of resuscitation interventions is discussed. The incidence of OHCA treated by emergency medical services varies throughout the world, but is in the range of 30 to 50 per 100,000 of the population. Survival-to-hospital-discharge rates also vary, but are in the range of 8 to 10% for many countries. Cardiac disease accounts for the vast majority of OHCAs; however, although it is a common cause of IHCAs, many other diseases are also common causes of IHCA. Five yearly reviews of resuscitation science have been facilitated in recent years by the International Liaison Committee on Resuscitation; these have been followed by the publication of regional resuscitation guidelines. There is good evidence that increasing rates of bystander cardiopulmonary resuscitation and earlier defibrillation are both contributing to improving the survival rate after an OHCA.
Keywords: cardiac arrest; cardiopulmonary resuscitation; outcomes; guidelines